Small Non-coding Transfer RNA-Derived RNA Fragments (tRFs): Their Biogenesis, Function and Implication in Human Diseases - Yu Fu; Inhan Lee; Yong Sun Lee; Xiaoyong Bao (Genomics & Informatics)
tRNA-derived RNA fragments (tRFs) are an emerging class of non-coding RNAs (ncRNAs). A growing number of reports have shown that tRFs are not random degradation products but are functional ncRNAs made of specific tRNA cleavage. They play regulatory roles in several biological contexts such as cancer, innate immunity, stress responses, and neurological disorders. In this review, we summarize the biogenesis and functions of tRFs.